f ( x ) = e cos x cos ( sin x )
Find the area bounded by f ( x ) and the x -axis between x = 0 and x = 2 π .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Ahh Nice one ! , Great to see that you know contour Integration
Log in to reply
Thanks. Yours is a nice method too :)
First use Eulers formula and convert given function to this :
f ( x ) = 2 e e i x + e − e i x A = ∫ 0 2 π 2 e e i x + e − e i x d x f ( x ) = 2 ( 1 + 1 ! e i x + 2 ! e 2 i x . . . . . . ∞ ) + ( 1 + 1 ! e − i x + 2 ! e − 2 i x . . . . . ∞ ) f ( x ) = 1 + 1 ! cos x + 2 ! cos 2 x + 3 ! cos 3 x . . . . . . ∞ A = ∫ d x + = 0 ∫ 1 ! cos x d x + 2 ! cos 2 x d x + 3 ! cos 3 x d x . . . . . . ∞ A = ∫ 0 2 π f ( x ) d x = 2 π
Q.E.D
P r o o f :: Proof of this above integral , i.e I = ∫ 0 2 π 1 ! cos x d x + 2 ! cos 2 x d x + 3 ! cos 3 x d x . . . . . . ∞ = 0
I = ∫ 0 2 π n = 1 ∑ ∞ n ! cos n x d x = n = 1 ∑ ∞ n ! 1 ∫ 0 2 π cos n x d x I = n = 1 ∑ ∞ n ! 1 [ n sin n x ] 0 2 π I = 0 H . P
A I 2 T S X right. Don't know how to solve this
See this note
Problem Loading...
Note Loading...
Set Loading...
Though I'm aware that the author of the question is looking for an 'elementary' solution, I will post my method just for reference and also to illustrate the power of complex analysis in cases like this one.
Let the given integral be I .
Also note that,
∫ 0 2 π e c o s x s i n ( s i n x ) d x = 0
Thus, I = ℜ ( ∫ 0 2 π e c o s x ( c o s ( s i n x ) + i s i n ( s i n x ) ) d x ) I = ℜ ( ∫ 0 2 π e c o s x e i s i n x d x ) I = ℜ ( ∫ 0 2 π e c o s x + i s i n x d x ) I = ℜ ( ∫ 0 2 π e e i x d x )
Let us first evaluate this integral and t h e n find it's real part.
So let e i x = z .
Then it is easy to see that z always lies on a unit circle centered at the origin and our integral is now a contour integral in the complex plane along this unit circle.
Now, i e i x d x = d z and thus,
I = ∮ ∣ z ∣ = 1 i z e z d z = ( 2 π ) 2 π i 1 ∮ ∣ z ∣ = 1 z e z d z
Finally, from Cauchy's integral formula ,
I = 2 π d z d z = 0 ( e z ) = 2 π
This completes the proof. Note that the imaginary part of our integral turns out to be zero as expected.
Edit: Well, I seem to have found an 'elementary' method as well.
We start with what we already proved: I = ℜ ( ∫ 0 2 π e e i x d x )
Now, e z = 1 + z + 2 ! z 2 . . . is an identity that holds in the complex domain as well.
Using this fact: I = ℜ ( ∫ 0 2 π 1 + e i x + 2 ! ( e i x ) 2 . . . d x ) ℜ ( x + i e i x + i ∗ 2 ∗ 2 ! e 2 i x + i ∗ 3 ∗ 3 ! e 3 i x . . . ) ∣ 0 2 π Thus, I = 2 π . (As all the terms containing e i x evaluate to zero)